CHILD MENTAL HEALTH PROMOTION IN WETLAND COMMUNITIES: A LITERATURE REVIEW - Wilma Hannie Daniel (Indonesian Global Journal Of Medical Research and Development, 2026)
Background: Child mental health is a global public health priority. Wetland communities face unique environmental, social, and health challenges that may influence child well-being. Objective: To review evidence on child mental health promotion in wetland and comparable vulnerable communities. Methods: A narrative literature review was conducted using peer-reviewed articles, systematic reviews, and international reports published between 2016 and 2026. Literature was retrieved from PubMed, ScienceDirect, Google Scholar, and institutional publications from the World Health Organization (WHO), UNICEF, and other relevant organizations. A thematic synthesis approach was used to identify recurring concepts related to child mental health promotion. Results: Evidence consistently identifies family support, school connectedness, resilience skills, social-emotional learning, cultural identity, and community engagement as major protective factors. Risk factors include poverty, environmental vulnerability, educational inequities, and psychosocial stressors. School-based interventions improve emotional competence, resilience, and mental well-being. Community-based and culturally responsive approaches strengthen identity and belonging. Emerging evidence also supports arts-based and participatory approaches. Conclusion: Child mental health promotion in wetland communities should be understood as a multidimensional ecological process involving children, families, schools, culture, and community systems. Future programs should integrate local wisdom, resilience-building, and culturally grounded health promotion strategies.